Rediseño geométrico y estrutural de la vía: El triunfo - Palo marcado, dese la abscisa 6+000 a las 12+000 Km., del cantón Pasaje, provincia de El Oro. - Lafebre Ibañez, Boris Fabricio (2015)
The current poor state of the road "El Triunfo - Palo Dial" Canton Pasaje, El Oro province, does not allow progress and improving the quality of life of these communities, because the current path in the rainy season is It becomes almost impassable. The main objective of this project is, to make the geometric and structural redesign of the track "El Triunfo - Palo Dial", to provide the way for further study of horizontal curves and vertical to give greater fluidity, safety and visibility on the road to ensure the inhabitants of the areas served safe and permanent transport route. The methodology used for this study is based on research through literature sources, consultations through the Internet, in addition to exploratory research, to know the physical characteristics of the study area. This project was designed according to the needs of the sector, optimizing resources to make the project environmentally and economically feasible during construction and during its useful life, the length of the track is 5147.15m, being a road of IV order according to the classification of MTOP, the same throughout its development has 10 pipe culverts reinforced concrete and side ditches on both sides of the road. It is recommended meet the specifications and design standards given by the MTOP, as well as applying the environmental management plan during and after construction of the road.